RI 3327 Behavior Of Flame Safety Lamps In Mine Atmospheres Deficient In Oxygen ? Introduction (1753def1-4dec-4d77-8daf-36801f1e1c43) - A. B. Hooker (The National Institute for Occupational Safety and Health (NIOSH), 1937)
All state mining laws require that flame safety lamps be used in gassy mines; the laws of some States require that safety lamps be kept for emergencies at every coal mine, whether gassy or nongassy. The use of the flame safety lamp has been widespread because it is the only defice readily available for detecting both the presence of methane and deficiency of oxygen. This paper reports the results of an investigation by the Electrical Section, in cooperation with the Gas Section, of the Pittsburgh Experiment station relative to the behavior of permissible flame Safety lamps in mine atmospheres deficient in oxygen and the effects of methan5/ on the detection of oxygen deficiency.